Evaluating the Efficacy of a Structured Teaching Program on Food Hygiene Knowledge and Practices Among Rural Household Members in Chhattisgarh, India - Ghosh, Robin (Journal of Educational Research and Policies, 2025)
Background: A food is a substance taken into the body to maintain life. Food hygiene are the conditions and measures necessary to ensure the safety of food from production to consumption. The primary aim of food hygiene is to prevent food poisoning and other food borne illnesses. The food hygiene is mainly categorized into milk hygiene, meat hygiene, egg hygiene and hygiene of fruits and vegetables. Food hygiene and safety prevent germs from multiplying in foods and reaching dangerous levels. Objective: To assess the pretest and posttest knowledge and practice of food hygiene among family members. To evaluate the effectiveness of structure teaching programme regarding food hygiene among family members. Methodology: Pre-experimental, one group pre-test post-test design was adopted for this study.60 family members were selected from Balod by using simple random sampling method for this study. A pretest was conducted by using structured knowledge questionnaire and check list for practice to assess the effectiveness of STP on knowledge and practice regarding food hygiene among family members. Result: Pre-test practice mean was13.5, mean percentage was 67.5% and standard deviation was 4.72 After the teaching programme mean was 17.84, mean percentage was 89.2%, The standard deviation was 2.57. the paired t-test value is 12.29, (df 59) was greater than table value 2.00 at 0.05 level of significance which proves the effectiveness of structured teaching programme.